Characterizing the Heterogeneity of Aging: A Vision for a Staging System for Aging - Jaul, Efraim; Barron, Jeremy (Frontiers in Public Health, 2021)
Introduction: Older adulthood encompasses several decades of enormous change and remarkable heterogeneity. Health providers have no formal strategy for defining older adult subpopulations. Methods: Using PubMed and Google searches, we reviewed literature on age-related physiologic, disease, functional, emotional and social changes. Results: We borrow from oncology a "TNM" (tumor size, lymph nodes, metastasis)- type staging system, with domains being chronologic age stratum, function, disease burden age stratum and life expectancy. Describing five chronologic age strata beginning at age 50 and five functional age strata. We provide clinical considerations and anticipatory guidance topics for each of the age strata and functional strata. Conclusion: Chronologic age, functional status, chronic disease burden, and life expectancy are important domains which impact clinical care and appropriate anticipatory guidance for individual older adults. Better strategies for differentiating subpopulations of older adults improve clinical care, reduce medical overuse, and improve personalized anticipatory guidance provided patients and families.